« Pourquoi vous être mariée si vous ne voulez pas d’enfants ? » Le travail contraceptif au Gujarat, Inde - Lucia Gentile (Centre Urbanisation Culture Société (UCS) de l'INRS, 2021)
Research Framework: The Indian Constitution guarantees the right to reproductive autonomy, including the right to access contraception. However, women continue to face significant barriers to reproductive autonomy and female sterilization remains the most commonly used method. Objectives: This article looks at the configuration of women’s contraceptive work in Bhuj (Gujarat, India), highlighting the material, financial and temporal constraints that still limit their reproductive autonomy. This paper aims to highlight the way in which women users of family planning services respect, criticize or circumvent social and legal injunctions regarding contraception. Methodology: This research is based on ethnographic fieldwork conducted between 2015 and 2018 in a public hospital in the city of Bhuj (Gujarat, India) and interviews with 40 women. Results: Because of the modesty that surrounds sexuality and the social disapproval of the manifestation of sexual desire, women hide the contraceptive work that they produce. Contraception is not only an invisibilized procreative work, but it must also be invisibilized by the users, in order to have a reproductive autonomy. This is one of the reasons that contribute to the increase use of sterilization, which is the preferred method of birth control in Bhuj today. Conclusions: The division of contraceptive labour contributes to and reinforces social and gender inequalities. Contraception is asserted as a responsibility that women must manage, even if several forms of authority influence this management. However, through a trade-off between the advantages and disadvantages of the different methods, women demonstrate a pragmatic agency that allows them to regulate their reproductive journey and to affirm their sexual identity as fertile women. Contribution: The article aims to update existing research on family planning in India, by mobilizing the notion of contraceptive work.